Maintenance of mesophyll potassium and regulation of plasma membrane H+-ATPase are associated with physiological responses of tea plants to drought and subsequent rehydration - Zhang, Xianchen; Wu, Honghong; Chen, Linmu; Liu, Linlin; Wan, Xiaochun (The Crop journal, 2018)
Drought stress is one of the main factors limiting yield in tea plants. The plant cell's ability to preserve K+ homeostasis is an important strategy for coping with drought stress. Plasma membrane H+-ATPase in the mesophyll cell is important for maintaining membrane potential to regulate K+ transmembrane transport. However, no research to date has investigated the possible relationship between plasma membrane H+-ATPase and mesophyll K+ retention in tea plants under drought and subsequent rehydration conditions. In our experiment, drought stress inhibited plasma membrane H+-ATPase activities and induced net H+ influx, leading to membrane potential depolarization and inducing a massive K+ efflux in tea plant mesophyll cells. Subsequent rehydration increased plasma membrane H+-ATPase activity and induced net H+ efflux, leading to membrane potential hyperpolarization and thus lowering K+ loss. A first downregulated and then upregulated plasma membrane H+-ATPase protein expression level was also observed under drought and subsequent rehydration treatment, a finding in agreement with the change of measured plasma membrane H+-ATPase activities. Taken together, our results suggest that maintenance of mesophyll K+ in tea plants under drought and rehydration is associated with regulation of plasma membrane H+-ATPase activity.